2021
DOI: 10.1111/omi.12356
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the yqeK gene leads to the accumulation of Ap4A and reduced biofilm formation in Streptococcus mutans

Abstract: Diadenosine‐5′,5′′′‐P1, P4‐tetraphosphate (Ap4A) is a second messenger playing a crucial role in various life activities of bacteria. The increase of Ap4A expression is pleiotropic, resulting in an impairment in the formation of biofilm and other physiological functions in some bacteria. However, Ap4A function in Streptococcus mutans, an important pathogen related to dental caries, remains unknown. In this work, the Ap4A hydrolase, YqeK, was identified and characterized in S. mutans. Then, the effects of yqeK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…All four compounds show zero violations of the Lipinski rule. As only molecular docking is done in this study, further in vitro studies can be done on M. koenigii to find properties like antioxidant, antidiabetic, anticancer, and anti-inflammatory and can infuse the compounds of this plant into herbal medicines [14][15][16][17][18].…”
Section: Parametersmentioning
confidence: 99%
“…All four compounds show zero violations of the Lipinski rule. As only molecular docking is done in this study, further in vitro studies can be done on M. koenigii to find properties like antioxidant, antidiabetic, anticancer, and anti-inflammatory and can infuse the compounds of this plant into herbal medicines [14][15][16][17][18].…”
Section: Parametersmentioning
confidence: 99%
“…Zheng et al . showed that the in-frame deletion of the yqeK gene in S. mutans causes an increase in the intracellular Ap4A levels, while biofilm formation and water-insoluble exopolysaccharides production are decreased [ 30 ]. The knockout of the yqeK gene leads to the downregulation of important virulence genes related to biofilms, such as gtfB , gtfC , and gtfD [ 30 ].…”
Section: Regulatory Formation Of S Mutans Biofilm ...mentioning
confidence: 99%
“…showed that the in-frame deletion of the yqeK gene in S. mutans causes an increase in the intracellular Ap4A levels, while biofilm formation and water-insoluble exopolysaccharides production are decreased [ 30 ]. The knockout of the yqeK gene leads to the downregulation of important virulence genes related to biofilms, such as gtfB , gtfC , and gtfD [ 30 ]. Although the mechanisms involved in the role of Ap4A need to be further investigated, these results suggest that it affects biofilm formation in S. mutans by affecting the expression of gtf s and the activity of Gtfs.…”
Section: Regulatory Formation Of S Mutans Biofilm ...mentioning
confidence: 99%
See 1 more Smart Citation